Faktor Penggunaan APD Pada Nelayan Tangkap - Harisah Harisah (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2023)
Increased awareness of using Personal Protective Equipment (PPE) for fishermen in Mate'ne, Tanete Rilau Village, Barru Regency, to reduce the risk of work accidents that often occur. This report discusses the factors affecting using Personal Protective Equipment (PPE) in capture fishermen. This study used a Cross-Sectional Study approach and involved 48 respondents. The results of the multivariate analysis showed that the most dominant variable affecting the use of PPE was family support. Family support significantly influences PPE use, with an Exp(B) value of 53,000. It can be concluded that family support is very influential in encouraging fishermen to use PPE when fishing at sea. Family support is the most dominant factor affecting the use of PPE. Health education efforts, awareness campaigns, and more supportive local cultural changes are needed to increase the use of PPE. This research provides important insights to improve occupational safety awareness and behavior among capture fishers.